Differences in salivary hormones and perception of exertion in elite women and men volleyball players during tournament - Penailillo, L. E.; Escanilla, F. A.; Jury, E. R.; Castro-Sepulveda, M. A.; Delicgue, L.; Zbinden-Foneca, H. P. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Sports tournaments induce both psychological and physiological stress, which seems to be different between men and women. Competition induces anticipatory rises in testosterone and cortisol levels, which may affect performance and physical exertion during tournaments. The aim of this study was to compare the changes in salivary cortisol and testosterone concentrations between men and women during an official volleyball tournament and to test potential correlations between changes in these hormones and perceived exertion after match. METHODS: Three matches of each team were assessed in the group stage of the Men and Women South American Volleyball Championship. Salivary cortisol and testosterone levels were measured in the fasting state, before and after each match. The rate of perceived exertion (RPE) was assessed after each match. RESULTS: Fasting cortisol concentrations were higher in women than men (~25%, P<0.001) while fasting testosterone was higher in men than women (~46%, P<0.001). Cortisol concentration increased only after the second match in men (+53.7%, P<0.001). Testosterone concentration was low before and after the third match in men (P<0.001) while it was elevated after the third match in women (P=0.003). The rate of perceived exertion was correlated with the change in testosterone levels due to the matches in both women (r=0.33; P=0.04) and men (r=0.44; P=0.02), which was not observed for cortisol concentrations. CONCLUSIONS: These results indicate that women have higher fasting cortisol, but lower fasting testosterone concentrations than men during a volleyball tournament. Thus, hormonal responses of women and men are different and related to their effort during the matches.